Cost-effective abatement of ground-level ozone in cities and for larger regions: Implications of non-monotonicity - Ove Wolfgang (University of Oslo, Department of Economics, 2001)
Ground-level ozone concentrations have adverse effects e.g. on human health and crops. Ozone is not emitted, but atmospheric reactions involving nitrogen oxides (NOx) and volatile organic compounds (VOCs) cause its formation. However, functions that relate precursor emissions to ozone concentrations are typically neither convex nor monotonic. Others have shown that corner solutions, where only one emission type is abated, can be cost-effective since the ozone formation is non-convex. This paper shows that the non-monotonicity implies an even more radical abatement strategy in some cases: the optimal amount of NOx emitted can be larger than the amount emitted in no-control.
Keywords: Q25; H77; 330; Ground-level Ozone; Cost-effective Abatement; Non-monotonicity; Transboundary Air Pollution; Ozon; Luftverunreinigung; Grenzüberschreitende Umweltbelastung